Factors affecting the performance of low budget resources for research projects in national national university of colombia in 2010 a 2012 applicability (2014)
The public budget is the instrument where plans and projects are executed from the estimated revenues and expenditures in a fiscal year resources, this tool is used in the National University of Colombia to manage their resources in accordance with the mission of teaching, training and extension, as a public entity treated as a university autonomous entity. The budgetary autonomy of the University is based on defining their own rules for programming, budget approval, implementation, monitoring and evaluation of resources based on the essential elements of the Organic Budget. This paper analyzes the implementation of the budget funds available for research at the National Level in the Global Development Plan 2010-2012 to determine the factors that affect the low budget execution.